Evaluating Mathematical Literacy Among Pupils Using Early Grade Mathematics Assessment in East Sumba - Angu Bima, Stevvileny; Ndakularak, Iona Lisa; Nggaba, Mayun E; Randjawali, Erwin; Pakereng, Yulita Mila (Jurnal Paedagogy, 2023)
This study aims to evaluate the level of mathematical literacy among elementary school-aged children in one of the schools in Lewa Paku District, East Sumba Regency. This research employed a mixed method of quantitative and qualitative approaches. The participants in this study were 20 students (10 students with good grades and ten students with poor grades in class), teachers, the school principal, and the head of the Education Office of East Sumba. The research instruments were mathematical tests adapted from the Early Grade Mathematics Assessment (EGMA), key informant interview guidance applied to all the participants, and observation during the learning processes. The quantitative data was analyzed using the descriptive technique, while the qualitative collected data was processed by data reduction, data display, and conclusion. The findings showed that the mathematical literacy of the fifth grade was in a low category. Factors affecting the student's math skills were less learning media, less conducive classes, limited, outdated, and unattractive printed textbooks, inadequate learning and teaching facilities, and less trained teachers. This research finding provides relevant and timely information to support students' achievement by adjusting policies, reforming curricula or programs, and instructional practices. Also, the policymaker can evaluate the effectiveness of the current education programs to decide on better interventions in supporting the students to improve their understanding of early math concepts.